2004
DOI: 10.1021/jo035793x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary α-Deuterium Kinetic Isotope Effects:  Assumptions Simplifying Interpretations of Mechanisms of Solvolyses of Secondary Alkyl Sulfonates

Abstract: For solvolyses of 2-propyl and cyclopentyl sulfonates, logarithms of alpha-deuterium kinetic isotope effects (alpha-KIE) correlate linearly with logarithms of nucleophilic solvent assistance (NSA); correlations have the same slopes, but different intercepts, consistent with both solvent and structural effects on alpha-KIEs for heterolysis, further supported by recent theoretical and experimental data. It is argued that alpha- and beta-KIEs cannot yet distinguish between mechanisms proceeding via one or more tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…7 Bentley has questioned several assumptions within Shiner's model, including that single-step α-D KIEs for non-S N 2 mechanisms are independent of solvent, 8 and has suggested that solvolyses of secondary alkyl sulfonates can be rationalized by a model combining heterolysis with nucleophilic solvent participation. 9 Changing the solvent may also influence a KIE by affecting isotopically sensitive vibrational frequencies directly, regardless of the TS structure or the identity of a rate-determining step. This was recognized by Keller and Yankwich, who investigated simple models that might allow medium effects on heavy-atom KIEs to be estimated, 10−12 but their work seems to have been largely overlooked along with the wider issue.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Bentley has questioned several assumptions within Shiner's model, including that single-step α-D KIEs for non-S N 2 mechanisms are independent of solvent, 8 and has suggested that solvolyses of secondary alkyl sulfonates can be rationalized by a model combining heterolysis with nucleophilic solvent participation. 9 Changing the solvent may also influence a KIE by affecting isotopically sensitive vibrational frequencies directly, regardless of the TS structure or the identity of a rate-determining step. This was recognized by Keller and Yankwich, who investigated simple models that might allow medium effects on heavy-atom KIEs to be estimated, 10−12 but their work seems to have been largely overlooked along with the wider issue.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Changing the solvent can also alter a KIE indirectly by affecting the mechanism; in Shiner’s generalized model for solvolytic substitution at saturated carbon, changing the solvent may alter the identity of the rate-determining step, as indicated by the magnitude and direction of the measured 2° α-D KIE . Bentley has questioned several assumptions within Shiner’s model, including that single-step α-D KIEs for non-S N 2 mechanisms are independent of solvent, and has suggested that solvolyses of secondary alkyl sulfonates can be rationalized by a model combining heterolysis with nucleophilic solvent participation . Changing the solvent may also influence a KIE by affecting isotopically sensitive vibrational frequencies directly, regardless of the TS structure or the identity of a rate-determining step.…”
Section: Introductionmentioning
confidence: 99%
“…14 and has suggested that solvolyses of secondary alkyl sulfonates can be rationalized by a model combining heterolysis with nucleophilic solvent participation. 15 The very small influence of solvent on 2°α-D and β-D 3 KIEs for solvolysis of (1chloroethyl)benzene in aqueous ethanol of varying proportions might indicate subtle mechanistic change, 16 but it may be noted that the solvent mixtures considered were all polar (35 < ε < 55). KIEs may be influenced by solvation that affects isotopically sensitive vibrational frequencies directly, regardless of TS structure or the identity of a rate-determining step.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Changing the solvent can also alter a KIE indirectly by affecting the mechanism: in Shiner’s generalized model for solvolytic substitution at saturated carbon, changing the solvent may alter the identity of the rate-determining step as indicated by the magnitude and direction of the measured 2° α-D KIE . Bentley has questioned several assumptions within Shiner’s model, including that single-step α-D KIEs for non-S N 2 mechanisms are independent of solvent, and has suggested that solvolyses of secondary alkyl sulfonates can be rationalized by a model combining heterolysis with nucleophilic solvent participation . The very small influence of solvent on 2° α-D and β-D 3 KIEs for solvolysis of (1-chloroethyl)­benzene in aqueous ethanol of varying proportions might indicate subtle mechanistic change, but it may be noted that the solvent mixtures considered were all polar (35 < ε < 55).…”
Section: Introductionmentioning
confidence: 99%